Pendekatan Highest and Best Use dalam Pelestarian Bangunan Bersejarah - Danastri Yuwono, Aisyah Pratita; Khairunnisa, Amanda Aufa; Ikasanti, Mesa Noor; Adilah, Nada Haifa; Widiyani, Widiyani (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
The concept of "Highest and Best Use" (HBU) refers to the optimal utilization of a property that would result in the highest value or benefit. In the context of a heritage building, which conceives historical or cultural significance, adaptive reuse concept becomes particularly relevant. Adaptive reuse involves repurposing a heritage building, such as a former factory building, for a new function that aligns with its historical and architectural characteristics. This approach allows for the preservation of the building's heritage value while also meeting contemporary needs and promoting sustainable development. This study examined the incorporation of HBU features in the three conversions of historical former factory buildings into tourist attractions, namely De Tjolomadoe, Rumah Atsiri, and The Heritage Palace. This study utilized four dimensions of HBU—the legal, physical, financial, and the maximum production dimension—to evaluate the three previous cases that employed adaptive reuse strategies. Results indicated that De Tjolomadoe serves as a noteworthy illustration of the effective implementation of HBU in renovating historical buildings, as evidenced by its achievements.